Effects of Educational Videos to Increase Knowledge, Attitudes, and Sleep Quality of Pregnant Women with Chronic Energy Deficiency - Asmaryani Hasim; Andi Nilawati Usman; Deviana Soraya Riu; Ariyanti Saleh; Sharvianty Arifuddin; Saidah Syamsuddin (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Lack of knowledge and attitudes is factor in the unresolved problem malnutrition pregnant women. The purpose of this study was to analyze the effectiveness of nutritional education media and sleep quality to increase knowledge and attitudes of chronic energy deficiency pregnant women towards nutrition and sleep quality. The research used is quantitative, while the design uses a combination of research and development and quasi-experimental methods with pre-posttest design controls. The sample was 63 pregnant women who experienced chronic energy deficiency (CED). Sampling technique by means of total sampling. Data analysis showed that knowledge increased significantly after being given the video intervention (mean=57, SD=14.53), the control group was lower, namely mean=9.1, SD=20.24, attitudes increased in the intervention group (mean=65.0, SD=20.47), control group (mean=2.96, SD=20.56), sleep quality in the intervention group increased with an average mean=0.68, SD=1.69, control group mean=0.000, SD=0.894. The p-value of the Mann-Whitney test results for the variables of knowledge, attitudes, and sleep quality is 0.000 < (0.005), this shows that there are differences in knowledge and attitudes before and after the educational animated video. In Conclusions, education using animated videos on nutrition and sleep quality is effective in improving the nutritional status of pregnant women. These results imply the need for educational media designs with more attractive models and innovations with more intensive promotion methods. It is hoped that future research can examine more deeply the relationship between other factors that influence chronic energy deficiency in pregnant women, such as sleep patterns and family support.